Sprengel's Deformity Associated with Musculoskeletal Dysfunctions and Renal Anomalies: A Case Report - Mohammad Hossein Kariminasab; Masoud Shayeste-Azar; Majid Sajjadi Saravi; Mehrdad Taghipour Gorgikolai (Case Reports in Medicine)
Background. Sprengel's deformity is a rare congenital anomaly of the shoulder girdle. The deformity is due to failure of descent of the scapula in intrauterine life. Case Presentation. We report a case of unilateral Sprengel's deformity associated with several other musculoskeletal and renal disorders consisting of absence of pectoralis major, weakness of trapezius and serratus anterior muscles, one kidney agenesis, and severe hydronephrosis of the other kidney in a 7-year-old boy. Conclusion. Sprengel's deformity can be associated with other musculoskeletal abnormalities and it is much more than a cosmetic problem.